What outcomes are important to families with a lived experience of stillbirth? A qualitative study to inform the development of a core outcome set for stillbirth care - Danya Bakhbakhi; Christy Burden; Anna Davies; Abigail Fraser; Dimitrios Siassakos; Mary Lynch; Laura Timlin; James M. N. Duffy; Maggie Redshaw; Heatherjane Dangerfield; Alexander E. P. Heazell; Lisa Hinton (PLoS ONE, 2026)
Objective To identify outcomes that are important to families, to inform the development of a core outcome set for stillbirth care research. Design Qualitative interview study. Setting A national study in the United Kingdom. Population A diverse sample of parents with a personal history of stillbirth were interviewed. Methods Data collection, coding and analysis were influenced by a modified Grounded Theory approach. Parents’ lived experiences of stillbirth were translated into outcomes for the purpose of developing a core outcome set. Results Forty parents and family members were interviewed. Analysis identified 349 potential care outcomes, 303 (87%) of which have not been previously reported by stillbirth care studies. Outcomes were organised into four major care outcome themes: 1) Clinical 2) Mental health and wellbeing 3) Social and family 4) Future pregnancy and children. Short- and long-term outcomes related to the labour, birth, investigations to understand why a baby had died, stillbirth in a multiple pregnancy, postpartum, psychological and subsequent pregnancy care were reported. Outcomes infrequently measured in previous stillbirth care research yet discussed by most participants were social isolation, impact on occupation and need for mental health support. Parents spoke of the importance of counselling to help them understand their grief, however, the provision of this service was reported to be varied throughout the UK. Conclusion A comprehensive outcome inventory has now been constructed, from which the final core outcome set will be determined. Future care should be developed and evaluated using outcomes that directly relate to the lived experiences of parents and families exposed to stillbirth.